Structural, physical, optical, mechanical, and radiation shielding investigation of tantalum pentoxide doped Germanate-Tellurite-Borate based glass system - M.I. Sayyed; M.H.A. Mhareb; M.Kh. Hamad; Abed Jawad Kadhim; Kawa M. Kaky; Yasser Maghrbi (Results in Physics)
A set of glass samples has been fabricated of tantalum, borate, germanate, tellurate, magnesium with glass formula of 20TeO2-35MgO-(35-x)B2O3-10GeO2-xTa2O5 where x refers to the concentration of Ta2O5 with values (0.5, 1.0, 1.5, 2.0, and 2.5) all in mol%. The melt followed by annealing process was utilized to produce these glasses. The amorphous nature of the glass systems was explored via XRD with a specific setup ranging from 10 to 80 degrees. Optical absorption with wavelengths shifted from low (358 nm) to high (382 nm) wavelength due to the addition of Ta2O5. Optical band gap (Eg) values are 3.720, 3.533, 3.480, 3.440, and 3.407 eV for Ta0.5, Ta1.5, Ta2.0, and Ta2.5. Several optical parameters were calculated in this work, such as optical basicity (Λ), metallization, transmission (T), reflection loss (R), electron polarizability (αo), and optical electronegativity (χ). Using density, dissociation energy (Gt), and packing density (Vt), the mechanical features were estimated based on the Makishima and Mackenzie model. Based on Vt and Gt values, several parameters were determined, such as fractal bond conductivity (d), longitudinal modulus (L), Young’s modulus (Y), oxygen packing density (OPD), microhardness (H), oxygen molar volume (OMV), shear modulus (S), bulk modulus (B), and Poisson ratio (σ). The ionizing radiation shielding properties of the prepared samples were systematically studied. The results confirmed that increasing Ta2O5 content enhances different radiation shielding parameters. At 0.05 MeV, the linear attenuation coefficient (LAC) is approximately 100 cm−1 for the Ta0.5 sample, while it is higher for the Ta2.5 sample, reaching around 105 cm−1. In addition, the kinetic energy released per unit mass (KERMA) value for the Ta0.5 sample near the K-edge is about 0.85 relative to air, increasing to approximately 0.89 for the Ta2.5 sample, indicating a 4.7 % enhancement. Moreover, the half-value layer (HVL) at 0.05 MeV is reduced from about 0.15 cm for the Ta0.5 sample to 0.14 cm for the Ta2.5 sample. This result demonstrates superior shielding performance compared to various traditional shielding materials. The high-density nature of these glasses makes them promising candidates for radiation protection applications.